THE EFFECTIVENESS OF EXERCISE THERAPY TO IMPROVE PATIENTS WITH STROKE CONDITIONS: SYSTEMATIC REVIEW - Yoel Kristian Adi Candra; Daniel Saka Pratama; Mianti Nurrizky Sutejo (Physiotherapy and Physical Rehabilitation Journal, 2022)
Background : According to the World Health Organization (WHO) stroke is a symptom that is defined as a functional brain disorder that occurs suddenly with clinical signs and symptoms both focal and global lasting 24 hours or more. Stroke in Indonesia has also experienced an increase in prevalence. In Indonesia, this disease occupies the third position after heart disease and cancer. Therefore, from several studies that we have, giving exercise therapy is effective in improving patients with stroke. Research purposes: To determine the effectiveness of exercise therapy in improving patients with stroke. Methodology: A systematic review of an article related to providing exercise therapy to stroke patients. Results: With exercise therapy can provide a significant effect to improve the condition of stroke patients. Conclusion: Provision of exercise therapy can increase daily physical activity in patients with stroke conditions.